The Role of the Physician-Computer Interaction Interpretation of Scintigraphic Data - Höhne, H. K.; Pfeiffer, G. (Methods of Information in Medicine, 1974)
It is well known that the application of computers in scintigraphy largely improves the diagnostic value of scintigrams. The speed for finding the diagnosis and its reliability may be further enhanced by interactive data analysis, i.e. when different modes of data presentation and quantitative evaluation are offered to the physician without noticeable delay. As an example of the advantages of the interactive method some features of the system ISAAC (Interactive Scintigram Acquisition and Analysis with a Computer) are demonstrated.
Keywords: Scintigraphy; Interactive Systems; Man-Machine Comrmmication; Image Processing